Origin Myths, Contracts, and the Hunt for Pari Passu. Issue 1 (25th April 2012) - Weidemaier, Mark; Scott, Robert; Gulati, Mitu
<x xml:space="preserve">Abstract</x> We use interviews with corporate lawyers and a data set of contracts to explore an elite area of legal practice: sovereign bond lending. Sovereign debt lawyers work at prestigious global law firms, yet the contracts they produce include some terms that defy explanation. Lawyers often account for the existence of these terms through origin myths. Focusing on one contract term, the pari passu clause, we explore two puzzling aspects of these myths. First, we demonstrate that the myths are inaccurate as to both the clause's origin and the role of lawyers in contract drafting. Second, the myths often are unflattering, inaccurately portraying lawyers as engaged in little more than rote copying. We probe this disjuncture between the myths and lawyers' actual practices and explore why contracts origin myths might hold such appeal for this elite segment of the bar.